Model of State Defense Strengthening Responding to the Impact of Eliminating the Presidential Threshold in Order to Realize Inclusive Democracy - F. Harsono, Cecilia; Sutanto, Sutanto; S, Guntur; Andreas N, Djoko; Harefa, Faonaso (UNIVERSITAS PAKUAN, 2025)
This article discusses the prediction of Indonesian political dynamics in the future after the elimination of the presidential threshold by the Constitutional Court (MK). The method used is a mixture method, a qualitative approach with NVivo 12 software and an analysis of the quantitative approach using SEM PLS-4. Theresults of the study show that politics and democracy significantly affect the National Defense, with a coefficient of 0.468 and a P-value of 0.023, which means a significant effect on the 5% significance level. This indicates that political stability and democracy have a greater role in forming national defense. So the model of strengthening the coalition system in parliament can encourage interparty consensus to maintain government stability, ensure that defense policies continue to run, maintain the neutrality of the TNI, keep the National Police consistent, and commit to state security, and the role of society is still needed to oversee politics and democracy